A 700-year multiproxy reconstruction on the Argentinian Pampas inferred from the sediments of Laguna Blanca Grande - López Blanco, Charo (2021)
The Pampean region is a crucial area to obtain sensitive paleoclimatic lacustrine archives due to the presence of shallow environments in a territory non impacted by humans until the last centuries. In this study, we provide a paleoecological reconstruction for the last ca. 700 years based on a multiproxy lacustrine record from Laguna Blanca Grande, in Olavarría (Buenos Aires, Argentina). Our inferences, which were based on sedimentary properties, diatom, cladoceran and ostracod assemblages, offered interesting information about hydroclimatic variability and nutrient increase. Changes in relative abundances on diatoms, specifically on Aulacoseira granulata and Aulacoseira granulata var. angustissima and fragilariods, were used to infer shifts in nutrient conditions. The remainder proxies together indicated small lake level changes. Reconstructed hydroclimatic conditions in Laguna Blanca Grande are consistent with previous paleoecological inferences indicating a humid phase around ca. AD 1450 and progressive drier conditions ca. AD 1530–1900. A flood gate construction and an increase of nutrients in the lake revealed a higher human pressure due to population increase and land-use changes during the last century. Further studies on taxonomy and autecology of microcrustaceans are needed to effectively unlock the information contained in biological proxies from Sudamerican records.